Achieving enhanced strength-ductility synergy in ZTC4 titanium alloy through hot oscillatory forging - Dejian Sun; Han Zhang; Mengwei Yang; Jingshu Yuan; Yuyang Yuan; Tianzi Wang; Yang Gao; Lei Fan; Xiaoqin Guo; Linan An (Journal of Materials Research and Technology)
The coarse Widmanstätten microstructure and high porosity of cast ZTC4 titanium alloy critically impair its mechanical properties and limit its industrial applications. In this study, the ZTC4 alloy was processed through a novel hot oscillatory forging (HOF) technique and conventional hot forging (HF), both achieving a deformation level of 64 %. The HOF-processed samples exhibited exceptional room-temperature tensile properties with an ultimate tensile strength of 943 MPa and elongation of 16.7 %. These values not only significantly surpassed those of HF-processed samples (822 MPa, 14.5 %), but also exceeded the performance of high-strain (180 %) isothermal multidirectional forged counterparts (921 MPa, 12.1 %). The enhanced mechanical properties are attributed to porosity reduction and grain refinement resulting from the application of oscillatory pressure during processing.